2010
DOI: 10.1007/s10517-010-1069-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Study of Species and Strain Variability in Bifidobacteria Population in Intestinal Microflora of Breast-Fed Infants and Their Mothers

Abstract: Qualitative and quantitative composition of enteric bifidoflora was studied in a group of 13 mother-infant pairs. Pure cultures of Bifidobacterium strains were isolated from feces and their species were identified by PCR with species-specific primers or by partial sequencing of 16S rDNA. The strains were compared by REP-PCR. The most incident Bifidobacterium species in mothers were B. longum and B. adolescentis. The infants were mainly colonized by B. bifidum and B. longum. The mother and her baby were coloniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Using PFGE, Bifidobacterium breve strains were shown to be identical, which to date provides the strongest support for the hypothesis of bacterial translocation and the presence of a bacterial entero‐mammary pathway, and subsequent vertical transfer and colonization of the neonatal gut via breast feeding, as suggested previously (Martín et al ., ; Perez et al ., ). Sharing of viable strains of Bifidobacterium longum , as well as Lactobacillus casei between maternal and neonatal faeces has furthermore been shown in the present study, and has recently been reported by other researchers for Bifidobacterium spp (Kulagina et al ., ; Takahashi et al ., ; Makino et al ., ). However, in these studies no link to breast milk was made and transfer via the vaginal microbiota during birth cannot be excluded.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using PFGE, Bifidobacterium breve strains were shown to be identical, which to date provides the strongest support for the hypothesis of bacterial translocation and the presence of a bacterial entero‐mammary pathway, and subsequent vertical transfer and colonization of the neonatal gut via breast feeding, as suggested previously (Martín et al ., ; Perez et al ., ). Sharing of viable strains of Bifidobacterium longum , as well as Lactobacillus casei between maternal and neonatal faeces has furthermore been shown in the present study, and has recently been reported by other researchers for Bifidobacterium spp (Kulagina et al ., ; Takahashi et al ., ; Makino et al ., ). However, in these studies no link to breast milk was made and transfer via the vaginal microbiota during birth cannot be excluded.…”
Section: Discussionmentioning
confidence: 97%
“…In previous research, transfer of Bifidobacterium spp. from maternal to neonatal gut (Kulagina et al, 2010;Takahashi et al, 2010;Makino et al, 2011), transfer of orally administered Lactobacillus spp. from maternal gut to breast milk (Jimenez et al, 2008a;Abrahamsson et al, 2009;Arroyo et al, 2010), or transfer of Bifidobacterium and Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…A second caveat of molecular methods is the low amount of DNA typically extracted from milk samples, making the relative proportion of contaminant DNA from sample manipulation and from DNA extraction reagents more important than when analyzing other biological samples, such as feces [ 33 , 38 ]. However, the role of breastfeeding in the vertical mother-to-infant transfer of specific bacterial strains (including bifidobacteria and lactic acid bacteria strains) has already been demonstrated [ 6 , 16 , 31 , 33 , 34 , 35 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Some studies have revealed the ability of certain gut bacteria to spread to extra-digestive locations in healthy hosts [ 46 , 47 , 48 , 49 , 50 ], while others (including in vitro, animal, and human studies) have shown that physiological bacterial translocation during late pregnancy has a scientifically plausible basis and may involve complex interactions between microbes, immune cells, and gut epithelial cells [ 4 , 5 , 6 , 16 , 47 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, without confirming the presence of these populations by culture, isolation, and strain level discrimination, it remains unclear whether human milk is a source of viable gut-associated obligate anaerobes or if dead cells or parts thereof are transferred to the breast-fed neonate (7). However, transfer of bifidobacteria, lactobacilli, and/or other bacteria at the strain level from the maternal gastrointestinal tract to the neonatal gut (39)(40)(41), from the maternal gastrointestinal tract to human milk (42)(43)(44), from milk to the neonatal gastrointestinal tract (3,6), and from the maternal gastrointestinal tract to milk and the infant gastrointestinal tract (5,7) has also been demonstrated by using culture and strain-level discrimination. Such studies reinforce the hypothesis that at least some bacteria, including obligate anaerobes, may be vertically transferred from mother to neonate via breastfeeding.…”
Section: Infant's Mouth and Maternal Skin As Potential Sources Of Bacmentioning
confidence: 99%